Fire safety measures in subway: lessons from past disaster - Kim, Yong Han; Kim, Se Hun; Ko, Myoung Jin (International Journal Of Community Medicine And Public Health, 2017)
On February 18, 2003, major catastrophe happened in Daegu, South Korea. 192 people were dead and 151 were injured from subway fire that one man carried out arson inside train.Inadequate emergency equipment and wrong disaster plan lead to many victims.